Association among peer substance use, religiosity and substance abuse in high school students - Uba, Ikechukwu; Yaacob, Siti Nor; Abu Talib, Mansor; Abdullah, Rohani; Mofrad, Sakineh (Medwell Journals, 2014)
This study examined the association among peer substance use, religiosity and substance abuse. The respondents of the study were 352 adolescents aged 13-18 years from Somolu, Lagos, Nigeria. The participants completed three validated instruments measuring, peer substance use, religiosity and substance abuse. The result indicated a partial mediation effect of religiosity in the relationship between peer substance use and substance abuse. Recommendations of the study highlighted the ameliorative capabilities of religiosity and its importance in the upbringing of a child.